Asymptotic Expansions for One-Phase Soliton-Type Solutions of the Korteweg-De Vries Equation with Variable Coefficients - Samoilenko, V. G.; Samoilenko, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We construct asymptotic expansions for a one-phase soliton-type solution of the Korteweg-de Vries equation with coefficients depending on a small parameter.